(998) Development alternatives in Egypt in 1974-75 بدائل التنمية في مصر في الفترة 1974-1975 - صقر احمد صقر (معهد التخطيط القومي, 2026)
ملخص The purpose of this study is to construct a macro economic model for Egypt that can be used for the purpose of projection planning. The model divides the economy into the following sectors: Three production sectors (industry, agriculture, and services), household, government, finance and foreign sectors. The model defines the major economic flows in the economy, as well as defining the major limits to growth by 37 variables. To determine the values of these variables in the target year (1974/75), 37 independent equations are postulated. تهدف هذه الدراسة إلى بناء نموذج اقتصادي كلي لمصر يمكن استخدامه لأغراض التخطيط الاستشرافي. ويقسّم النموذج الاقتصاد إلى القطاعات التالية: ثلاثة قطاعات إنتاجية (الصناعة، الزراعة، والخدمات)، بالإضافة إلى قطاع الأسر، وقطاع الحكومة، والقطاع المالي، والقطاع الخارجي. كما يحدد النموذج التدفقات الاقتصادية الرئيسية داخل الاقتصاد، إلى جانب تحديد القيود الأساسية على النمو من خلال 37 متغيرًا. ولتحديد قيم هذه المتغيرات في السنة المستهدفة (1974/1975)، يتم افتراض 37 معادلة مستقلة.